Art therapy is associated with sustained improvement in cognitive function in the elderly with mild neurocognitive disorder: Findings from a pilot randomized controlled trial for art therapy and music reminiscence activity versus usual care - Mahendran R. (BioMed Central Ltd., 2020)
10.1186/s13063-018-2988-6